MEMBENTUK KARAKTER SISWA MELALUI METODE KISAH QURANI - Mamik Rosita (IAIN Padangsidimpuan, 2016)
As direct practitioner, teachers have important role to understand and implement educational character in perfect reality. Teacher as curriculum practitioner required to understand educational character and have extensive knowledge about the method of planting character to the students. By listening a story will make them forming the visualization. Then, they will imagine the characters and situations in the story, then appearance in their hearts. This can inspire students to do something like that already made as in their hearts. Based on these, teachers need to select exemplary stories which can carry a positive message to the students, and Qur’anic story or the story from Al-Qur’an is the best story in the world. It has adopted good, exemplary, and islamic story. Qur’anic story in learning offers the solution to shape the students’ character especially in PAI subject. The story is able to make teachers and students have closer relationship as well as balancing television show. The implementation of Qur’anic story method in the PAI learning can be done by integrating